Activation of ROP6 GTPase by Phosphatidylglycerol in Arabidopsis - Han, Xiuli; Shi, Yue; Liu, Guoyong; Guo, Yan; Yang, Yongqing (Frontiers in Plant Science, 2018)
Plant Rho-like GTPases (ROPs) are switch-like proteins which play essential roles in controlling cell polarity development and cellular activities. ROPs are regulated by many factors, such as auxin, light, and RopGEFs and RopGAPs proteins. However, it has not been reported yet whether small molecules play a role in the regulation of ROP activity. Here, we showed that AtROP6 specially bound to a phospholipid, phosphatidylglycerol (PG), by the protein-lipid overlay and liposome sedimentation assays, and further MST assay gave a dissociation constant (Kd) of 4.8 ± 0.4 μM for binding of PG to His-AtROP6. PG profile analysis in Arabidopsis revealed that PG existed both in leaves and roots but with distinctive fatty acyl chain patterns. By evaluating AtROP6 activity using RIC1 effector binding-based assay, we found that PG stimulated AtROP6 activity. In the FM4-64 uptake experiment, PG inhibited AtROP6-mediated endocytosis process. By evaluating internalization of PIN2, PG was shown to regulate endocytosis process coordinately with NAA. Further root gravitropism experiment revealed that PG enhanced the AtROP6-mediated root gravity response. These results suggest that the phospholipid PG physically binds AtROP6, stimulates its activity and influences AtROP6-mediated root gravity response in Arabidopsis.